(untitled) (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to determine the role of financial literacy as measured through financial behavior, attitude and skills towards the consumptive behavior of housewives in the city of Tasikmalaya. This research has a type of survey with an asociative causality characteristic that aims to be descriptive and verificative. The object of this study is a housewife in the city of Tasikmalaya, due to the unknown population size, the researchers used a non-probability sampling technique with a purposive sampling technique with 200 respondents. The approach used to determine the relationship between these latent variables is the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the Bootstrap parameter estimation method. The results of the research show that financial behavior has a positive effect on consumptive behavior, the more positive a person’s behavior in managing finances, the more aware of the consumptive behavior they are doing. Financial attitude has a positive effect on consumptive behavior, someone who understands how to spend, save, hoard and dispose of their money will be able to predict what they need or what is important for consumption. Financial skills influence consumptive behavior, the better the skills, the better the ability to make the right decisions in consuming something..